2021
DOI: 10.3389/fgene.2020.566497
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LncRNA Prognostic Markers for Ovarian Cancer by Integration of Co-expression and CeRNA Network

Abstract: BackgroundOvarian cancer (OC), one of the most prevalent gynecological malignancies, is characterized by late detection and dismal prognosis. Recent studies show that long non-coding RNAs (lncRNAs) in competitive endogenous RNA (ceRNA) networks influence immune infiltration and cancer prognosis. However, the function of lncRNA in OC immune infiltration and prognosis remains unclear.MethodsTranscriptomes of 378 OC samples and clinical data were retrieved from the TCGA repository. Modules related to immune cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…These results demonstrate that lncRNAs are promising prognostic markers in OC. An autophagy-related lncRNA prognostic signature for OC was constructed by Meng et al ( 35 ) and an immune-related lncRNA prognostic model for the prediction of survival in OC was established by Liang et al ( 36 ). However, it appears there is no evidence of a ferroptosis-related lncRNA prognostic signature in OC.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that lncRNAs are promising prognostic markers in OC. An autophagy-related lncRNA prognostic signature for OC was constructed by Meng et al ( 35 ) and an immune-related lncRNA prognostic model for the prediction of survival in OC was established by Liang et al ( 36 ). However, it appears there is no evidence of a ferroptosis-related lncRNA prognostic signature in OC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to construct a prognostic model which can predict the prognosis and immunotherapy response based on immune-related lncRNAs in ovarian cancer. Liang et al [32] used weighted gene co-expression network analysis (WGCNA) and found that the expression levels of 4 lncRNAs could be used as independent immune prognostic factors for OC. Liu et al [33] identified 52 lncRNAs as ovarian cancer-specific immune lncRNA and redefined two different molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…After identifying the miRNAs that overlapped between the miRDB and miRWalk website, the Cytoscape software was used to visualize the lncRNA-miRNA-mRNA ceRNA network. Finally, the GenCLiP310 website 7 was used to perform functional enrichment analysis to explore the functions of the genes in this ceRNA network ( Liang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%